Entrepreneurship and the different strategies to achieve business sustainability - Corimanya Diaz, Gaby Naldy (2023)
The objective of this research was to identify the different strategies that entrepreneurs use in their businesses to achieve sustainability. The methodology was qualitative, descriptive, non-experimental, exploratory, and explanatory, with a non-systematic literature review in open databases Scielo and Redalyc, with the keywords "entrepreneurship", AND "sustainability", "strategies", "competitive advantages". The inclusion criteria applied were papers between the years 2016 and 2023 only, in both Spanish and English, and answering the research question; a total of 448 papers were obtained. The exclusion criteria were: the papers from years before the range given, languages other than Spanish and English, and not related to the subject or research question. Convenience sampling was applied and 10 research papers were selected. The results indicated that the entrepreneurs applied strategies to minimize costs and expenses, to maximize profit, to manage warehouses and inventories adequately, to search for better suppliers, to constantly innovate in their products, services and processes, to implement new business models, to apply technology, to constantly motivate their workers, to develop skills, considering workers as the main element, to develop customer empathy skills, to develop planning strategies, to analyze the environment in search of new opportunities, organization, leadership of managers, to control through management indicators, to search for international markets, among others. The research concluded that there is a great diversity of strategies used by entrepreneurs to achieve business sustainability.